2019
DOI: 10.1634/theoncologist.2019-0751
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Sarcopenia and Systemic Inflammation on Survival in Patients with Advanced Stage Cancer Treated with Immunotherapy

Abstract: Background Sarcopenia and inflammation have been associated with poor survival in patients with cancer. We explored the combined effects of these variables on survival in patients with cancer treated with immunotherapy. Methods We performed a retrospective review of 90 patients enrolled on immunotherapy‐based phase I clinical trials at Emory University from 2009 to 2017. Baseline neutrophil‐to‐lymphocyte ratio, monocyte‐to‐lymphocyte ratio, and platelet‐to‐lymphocyte ratio (PLR) were used as surrogates of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…In their final point, Orlandella et al inquire whether we quantified sarcopenia in this analysis because the IFI was associated with worse outcomes in patients with a high SFI in our study. In a recently published article,3 our group shows that the presence of sarcopenia and systemic inflammation, measured by the platelet‐to‐lymphocyte ratio, was associated with decreased OS and PFS in this cohort of patients. In conclusion, we appreciate the thoughtful commentary from Orlandella et al and agree that the field of oncology would benefit from large, comprehensive studies elucidating the impact of host adiposity, including the different compartments, on survival in patients with cancer treated with immunotherapy.…”
mentioning
confidence: 72%
“…In their final point, Orlandella et al inquire whether we quantified sarcopenia in this analysis because the IFI was associated with worse outcomes in patients with a high SFI in our study. In a recently published article,3 our group shows that the presence of sarcopenia and systemic inflammation, measured by the platelet‐to‐lymphocyte ratio, was associated with decreased OS and PFS in this cohort of patients. In conclusion, we appreciate the thoughtful commentary from Orlandella et al and agree that the field of oncology would benefit from large, comprehensive studies elucidating the impact of host adiposity, including the different compartments, on survival in patients with cancer treated with immunotherapy.…”
mentioning
confidence: 72%
“…Several studies demonstrated that systemic in ammatory biomarkers in peripheral blood were predictive markers for treatment outcomes in different solid tumors including prostate, colorectal, and esophageal cancer, melanoma, and NSCLC [15][16][17][18][19]. Although the exact biological basis for these ndings has not been thoroughly elucidated, in ammatory cells such as neutrophils play a signi cant role in tumor development and progression via effects on tumor cells or other components of the tumor microenvironment by secreting chemokines and cytokines such as transforming growth factor-ß, interleukin-6 (IL-6), and matrix metalloproteinase [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been associated with increased levels of myostatin, a negative regulator of muscle mass [ 19 ], and skeletal muscle inflammation [ 20 ]. Sarcopenia has been observed in patients with chronic inflammatory conditions [ 21 ], and anti-inflammatory therapy reduces inflammation-induced muscle weakness [ 22 ]. Previous studies have suggested that inflammation parameters inversely correlate with muscle strength [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%